Drug Delivery and Monitoring through Wearable Devices with Microneedles in the Field of the Health Care System - Kumarswamy, K.C.; Madhu, B.K.; Naveen, N. R.; Goudanavar, Prakash S.; Purushotham, K.N. (Micro and Nanosystems, 2024)
Microneedles represent a revolutionary advancement in drug delivery and diagnostics, offering a minimally invasive approach to accessing the intricate biological environment of the human body. These micron-sized needles, typically ranging from 25 to 1000 micrometers in length, penetrate the outermost layer of the skin, creating microchannels that facilitate the transdermal administration of therapeutics or the extraction of interstitial fluid for analysis. This innovative technology holds great promise for enhancing patient compliance, reducing side effects, and improving the overall efficiency of drug delivery. Integrating microneedles with wearable devices further amplifies their potential impact. Wearable devices provide a seamless interface for monitoring and controlling microneedle-based systems, fostering real-time data collection and personalized healthcare. Such devices can be designed to administer precise drug doses at predetermined intervals, adapting treatment regimens to individual patient needs. Additionally, the combination of microneedles and wearable devices enables continuous monitoring of biomarkers through the extraction of interstitial fluid, offering a non-invasive method for disease diagnosis and management. The review also provides a detailed overview of the mechanisms, types, fabrication techniques, applications, and patents for integrating microneedles with wearable devices. This symbiotic relationship between microneedles and wearables opens new paths for patient-centric healthcare, with the potential to transform chronic disease management and streamline therapeutic interventions. As these technologies continue to evolve, their integration may pave the way for personalized, on-demand healthcare solutions, accompanying a new era of patient well-being and treatment efficacy.
Keywords: Wearable devices